Regulations For Implementing Passive Euthanasia In The Terminal Stage Patients (End of Life) Which Is In Accordance With Justice and Legal Certainty In Indonesia - Dian Andriani Ratna Dewi; Waty Suwarty Haryono; Evita Isretno Israhadi (Eduvest - Journal of Universal Studies, 2023)
Euthanasia is an act of intentionally not doing something aimed at prolonging someone's life or intentionally doing something to shorten or also end the life of a patient which is carried out to hasten his death, while enabling a good death without unnecessary suffering. Thus, in practice, in a terminal condition, a doctor may or may not perform an act that may result in the death of a patient in accordance with the written request of the patient/family. This dilemmatic condition requires legal certainty in order to uphold justice and humanity as well as legal protection. The problems are 1) How is passive euthanasia applied for terminal patients? 2) How is legal certainty in the application of euthanasia in Indonesia? 3) How is the implementation of euthanasia that meets the community's sense of justice? To answer these problems, a research using normative juridical methods is needed through primary data collection in the form of empirical data from interviews and filling out questionnaires about knowledge and level of agreement on euthanasia. Secondary data in the form of research on primary, secondary and tertiary legal materials. 8The results of the study show that the implementation of regulations in the Act and Ministerial Regulations that lead to the implementation of euthanasia has so far been applied, especially to terminal patients. However, the legal certainty of the act has not been clearly described because there are rules that are not in line. Euthanasia cannot be equated with ordinary homicide. To fulfill justice and humanity as well as legal protection, euthanasia regulations are needed in a harmonious positive law